2003
DOI: 10.1002/bio.727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight reduction on neutrophil phagocytic activity and oxidative burst activity in female judoists

Abstract: This study investigated the effects of short-term weight reduction on neutrophil functions in female judoists. Sixteen actively competing female judoists were divided into two groups. Eight who required weight reduction were defined as the weight reduction group, and the remaining eight were used as the control. Blood samples were taken before, immediately after and 8 days after the match. Phagocytic activity and oxidative burst activity of neutrophils were measured by flow cytometry. In the weight reduction g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 22 publications
3
33
0
6
Order By: Relevance
“…the neutrophil ROS production capability, PA and SOA, have demonstrated a variety of results after acute/single bout exercise. ROS production has been reported to increase (1,(8)(9)(10)(11), decrease (1,10,(12)(13)(14)(15)(16) and remain unchanged (13,(17)(18)(19). PA significantly decreased after intense exercise (1,10,11,16,(19)(20)(21) or increased, or did not change with exercise (1,10,12,15,22).…”
Section: Introductionmentioning
confidence: 91%
“…the neutrophil ROS production capability, PA and SOA, have demonstrated a variety of results after acute/single bout exercise. ROS production has been reported to increase (1,(8)(9)(10)(11), decrease (1,10,(12)(13)(14)(15)(16) and remain unchanged (13,(17)(18)(19). PA significantly decreased after intense exercise (1,10,11,16,(19)(20)(21) or increased, or did not change with exercise (1,10,12,15,22).…”
Section: Introductionmentioning
confidence: 91%
“…the neutrophil ROS production capability, phagocytic activity (PA) and serum opsonic activity (SOA), have demonstrated a variety of results after acute/single bout exercise. ROS production has been reported to increase (8)(9)(10)(11)(12), decrease (3,10,11,(13)(14)(15) and show no change (13,14,(17)(18)(19). PA significantly decreased after intense exercise (3,(10)(11)(12)(19)(20)(21) or increased or did not change with exercise (10,11,13,16,22).…”
Section: Introductionmentioning
confidence: 91%
“…However, instead of broadening the discussion with contrasting evidence, Dr Davis has chosen to criticise our choice of reference. To strengthen our argument, we wish to highlight a further seven studies which show impairment of selected parameters of immune function following RWL [20][21][22][23][24][25][26]. Furthermore, an increased incidence of upper respiratory tract infection due to RWL was reported in at least two studies [24,25], and confirmed by data from our own group which is currently under review.…”
Section: Dear Editormentioning
confidence: 55%